If 1/(x(a-x)) is equivalent to B(1/x + 1/(a-x)), Express 'B' in terms of 'a'

1/(x(a-x)) = B(1/x + 1/(a-x)) Note: the '≡' sign (defined equivalence) can be used in place of '=' but this is not necessary to achieve full marks.Step: multiply both sides by x(a-x)1 = (x(a-x))B(1/x + 1/(a-x))Step: Multiply out brackets containing functions of x1 = B((x(a-x)/x) + (x(a-x))/(a-x))Step: Simplify new function of x1 = B((a-x)+x)1 = B*aB = 1/a

Answered by Charles G. Maths tutor

3273 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Via the product rule, or otherwise, differentiate 'y = xsin(x)'.


Given that the graph f(x) passes through the point (2,3) and that f'(x)=6x^2-14x+3, find f(x).


Given a function f(x)=3x^2+5x-1, find its derivative.


A circle has equation x^2 + y^2 - 8x - 10y + 5 = 0, find its centre and radius


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences